The age at first consumption of forage in calves and its effect on growth and rumination in the short- and long-term - Jianxin Xiao; Tianyu Chen; Rong Peng; Gibson Maswayi Alugongo; Hui Yang; Muhammad Zahoor Khan; Shuai Liu; Yulin Ma; Jingjun Wang; Wei Wang; Yajing Wang; Shengli Li; et al. (Journal of Animal Science and Biotechnology, 2023)
Abstract Background Previous investigations into the effect of dietary forage on calf performance have been inconsistent, and there is a paucity of information exploring the effect of age on the growth performance and rumination of calves. Eighty-four female Holstein calves (41.5 ± 4.2 kg) were enrolled at birth, a subset of the calves were fed calf starter only (CON, n = 21) while the rest (n = 63) were classified into three treatment groups: the early (EHAY, n = 26, 5.1 ± 0.8 d), the middle (MHAY, n = 21, 7.9 ± 0.8 d) and the late (LHAY, n = 16, 12.1 ± 1.4 d) hay consumers. The short-term effect of the age at first forage consumption (AFF) on calves’ feed intake was monitored until d 84. In addition, the long-term effects of AFF on body weight, structural growth and rumination behavior were recorded until d 196. Rumen samples were collected on d 1, 7, 35, 84 and 196 to analyze the rumen fermentation, while fecal samples were collected from d 78 to 84 to estimate digestibility parameters. Results Treatment had no effect on feed intake. While, the EHAY calves tended to have lower BW and ADG compared to LHAY and CON calves. Several total-tract apparent digestibility parameters and digestible nutrients intake were significantly lower in EHAY calves compared with CON and LHAY calves. Calves in the EHAY group tended to begin ruminating ealier, while CON calves were the latest (12.3 vs. 15.5 days of age). A treatment and time interaction was present for rumination time due to greater rumination in calves consuming hay compared to CON calves in week 10 to 12, the differences in rumination disappeared afterwards, no long-lasting significant differences in the rumination and rumen fermentation parameters were found between treatments. Conclusions In conclusion, this study showed that hay consumption earlier in life (in the first week, around 5 days of life) could negatively affect the growth of the calf in the short and long term. Compared to consuming hay from the second week (around 12 days of life) or feeding concentrate only without hay, starting to consume hay from the first week could compromise nutrient digestibility and digestible nutrient intake independent of developing rumination behaviour and rumen fermentation.